(untitled) (TAMADDUN NURI JURNALI, 2025)
In narratology, plot denotes the arrangement of narrative events, as distinct from the chronological sequence of events (fabula). Originating with the Russian Formalists (Propp, Shklovsky), this concept emphasizes the artistic construction of a story’s order. This article surveys plot and its varieties-chronological, non-linear, concentric, associative, circular with comparative examples from Uzbek and world literature. It then focuses on the retrospective plot, a plot structure that begins with a present or culminating moment and then “looks back” to earlier events.